ANALISIS KESIAPSIAGAAN PEDAGANG DALAM PENANGGULANGANAN KEBAKARAN DI PASAR MASOMBA KOTA PALU - Firmansyah; Sadli Syam; Muhammad Sabri Syahrir; Muhammad Aji Satria; Rendhar Putri Hilintang (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2026)
ANALYSIS OF TRADERS' PREPAREDNESS IN FIGHTING FIRE IN MASOMBA MARKET, PALU CITY Fire is a disaster that can cause severe losses to managers, owners, users, and the surrounding community. Traditional markets are particularly vulnerable to fire incidents, with impacts ranging from economic damage to threats to human safety. This study aimed to analyze the preparedness of traders in fire disaster management at Masomba Market, Palu City, and to provide a basis for developing preparedness programs, including education, training, and fire drills. A mixed-method design with a concurrent triangulation approach was applied, integrating qualitative and quantitative methods equally. The study was conducted at Masomba Market, Palu City, from August to September 2025. The results showed no significant relationship between knowledge and attitudes with traders’ preparedness in fire prevention. However, training and counseling were positively associated with improved preparedness. Overall, traders demonstrated sufficient knowledge, attitudes, and participation in training, as supported by interviews and probing with informants. Nonetheless, some informants provided responses that diverged from general ethical norms. The study suggests that traders should actively engage in fire preparedness training and consistently apply the acquired skills in daily practices.